Australia : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
In this study, Australia's economic performance from the onset of the global financial crisis is discussed. A healthy banking system, flexible exchange rate, and robust demand for commodities from Asia are important for good performance. Although recent global market volatility has increased uncertainty about the economic outlook and tilted risks downward, strong commodity demand from emerging Asia underpins Australia's favorable economic prospects. The importance of tax and structural reforms is emphasized. The Australian Prudential Regulation Authority's plans are used to undertake stress tests incorporating disruptions to funding markets.